Diluted and concentrated organosols of fullerene C60 in the toluene–acetonitrile solvent system as studied by diverse experimental methods. Issue 4 (3rd April 2021) - Kyzyma, Olena A.; Mchedlov-Petrossyan, Nikolay O.; Turki Mahmood Al-Shuuchi, Younis; Tropin, Timur V.; Ivankov, Oleksandr I.; Kriklya, Nika N.; Gromovoy, Taras Yu.; Kryshtal, Aleksandr P.; Zhigunov, Alexander N.; Korosteleva, Elena A.; Shekhovtsov, Sergey V.; Garamus, Vasil M.; et al.
Abstract: In this article, we examined the state of fullerene C60 in toluene and its mixtures with acetonitrile in both diluted, (4.0 to 6.3)×10 −6 M, and concentrated, (0.23 to 1.9)×10 −3 М solutions, prepared by either equilibrium or non-equilibrium procedures. Typically, the working solutions were prepared by diluting stock solutions of fullerene in toluene. Some specific features of solid fullerene interaction with atmospheric oxygen were revealed using the LDI mass-spectrometry. A combination of electron absorption spectra of the fullerene in C6 H5 CH3 –CH3 CN mixtures with the analysis of the particle size distribution using the DLS method demonstrated that even in acetonitrile-rich media, where diluted C60 exists in colloidal state, some features of the molecular absorption spectra are still present. Such effect is in line with the formation of the large solvation shells of an aromatic solvent around fullerenes. The TEM images of the dried colloidal solutions demonstrate a loose floc configuration of the aggregates, contrary to the crystal structure of the species in a toluene-free C60 dispersion obtained by hand-grinding. In solution, the spectrum of the last-named is a monotonous curve increasing toward ultraviolet. The LDI measurements proved the tendency of C60 toward forming negative species under contact with acetonitrile. Electrophoretic studies state that a universal property of the negatively charged colloidal species is their expressed ability to overcharging in the presence of inorganic cations, which are poorly solvated by acetonitrile. In concentrated (oversaturated) fullerene solutions, where the SAXS and SANS methods are applicable, fractal-type aggregates of fullerenes were revealed in solutions. The analysis of aggregates structure indicates that their packing density is increased with growth of fullerene concentration and/or amount of acetonitrile in the mixture. Thus, branched aggregates were observed in toluene solution, while fullerenes form dense clusters with diffusive surface in mixtures with acetonitrile.